Case report: A novel de novo variant of NACC1 caused epileptic encephalopathy and intellectual disability - Wu, Jiahao; Gan, Jing; Hua, Yimin; Li, Yifei; Qie, Di (Frontiers in Psychiatry, 2024)
Background: Genetic disorders may also contribute to intellectual disability. Using the whole exon sequencing (WES), several variants are identified as autosomal dominant inheritance to intellectual disability. Thus, the WES application demonstrated a critical role in distinguishing intellectual disability in children patients, which provided essential diagnosis and promoted therapeutic strategy.The proband, an 18-month-old female, presented with a complex clinical profile characterized by profound developmental delay, epilepsy, and neurological developmental impairment. WES identified a heterozygous c.913A>G variant in exon 2 of NACC1, resulting in disease causing by amino acid sequence changed, protein features affected and splice site changes by MutationTaster analysis.The protein structure of NAC1 had been built and named AF-Q96RE7-F1, and the mutant site was beyond BTB/POZ, NLS and BEN domains. Then, Pymol software had been used to illustrate the molecular structure between wild type of mutant type of NAC1. The residues around 304 site of amino acid changed in NAC1 p.T304A with altered hydrogen bond, indicating an unstable structure. The patient was diagnosed with intellectual disability and profound developmental delay with epilepsy harboring a novel de novo NACC1 variant. Upon hospital admission, a comprehensive treatment regimen was initiated, including antiseizure medications, nutritional supplements, and rehabilitation training. As a consequence, the movement performance improved.However, the recurrent epilepsy attack still been occurred.This is the first case to reveal a novel NACC1 c.903A>G variant which induced neurological impairment in infant. And this report expanded the understanding of non-domain associated variant of NACC1 and developmental disorder.